Adsorption of Cadmium ion from aqueous solutions by stem and leaf of Parthenium hysterophorus - Yogenthiran, E.; Abiman, P. (University of Jaffna, 2021)
Cadmium is a toxic heavy metal causing risks for living organisms even at low levels of its presence. Poor treatment of Cd2+ from contaminated sources leads to high risks for human health causing health disorders like rheumatoid arthritis, kidney failure and allergies [1]. Parthenium hysterophorus is a non-living biomass of low cost, environment friendly bio sorbent and can be considered as a very effective adsorbent for the removal of heavy metals like Cd. Studies have been carried out on activated carbon prepared from parthenium for elimination of Cd and Ni from contaminated wastewater [2]. In this report we use dried plant parts of Parthenium hysterophorus as an adsorbent for the removal of Cd2+ ions from aqueous solution. The extent of adsorption of Cd2+ ions by stem and leaf parts of the Parthenium hysterophorus is analyzed by using acid and base activation, weight variation and concentration variation. Anodic Stripping Voltammetry (ASV) via standard addition technique was used in the quantitative determination of Cd2+ samples. Results show that the percentage adsorption of the Cd2+ ranges from 41.31 to 99.59. Different operational parameters observed during the process of investigation reveal that the adsorbent dosage, initial adsorbate concentration, activated adsorbent dosage govern the overall process of adsorption. The effective concentration of Cd2+ ion and the optimum dosage of Parthenium hysterophorus were calculated as 100 μM and 50 mg of acid activated leaf powder respectively. This results suggest that Parthenium hysterophorus can be used effectively to remove Cd2+ ions from wastewater.
Keywords: Heavy metal toxicity; Wastewater treatment; Parthenium hysterophorus